Penerapan Manajemen Sumber Daya Manusia dalam Meningkatkan Kompetensi Guru - Rolia Ade Astagini; Nur Izzatin Nadifah; Aisyah Dana Luwihta (AKSI: Jurnal Manajemen Pendidikan Islam, 2022)
This article is the result of a field study at MA Darussalam Daun on human resource management in improving teacher competence there. This study aims to answer academic problems according to the focus of the study, namely to determine the application of human resource management in improving the quality of education and to determine the factors and obstacles in improving the quality of education. Using qualitative methods with a phenomenological approach, data collection techniques by conducting observations, in-depth interviews and documentation, data analysis techniques used are data reduction, data presentation and conclusion drawing, data checking using data triangulation. The results of this study are 1) The application of human resource management in improving the quality of education starting with planning, organizing, directing, and controlling, 2) Supporting factors include support from parents, and involving teachers in training programs while the inhibiting factors are lack of discipline of teachers so that the application of human resource management is still perfunctory as well as the lack of facilities and infrastructure that can hinder the teaching and learning process.